Desenvolvimento de algoritmos e ferramentas de síntese e validação de estratégias para o controle em manobras ou navegação de veículos ou robôs móveis multi-articulados - Oliveira, Tiago Reinan Barreto de (2010)
In this work, an experimental platform was developed for testing maneuvers by vehicles or mobile robots multi-jointed, has also developed a fuzzy control algorithm and con guration made its analysis of performance against other algorithms in the literature. The platform built is comprised of an articulated vehicle multi-scale, composed of one element and two tractor trailers or passive elements. Were made and shipped some electronic circuitry responsible for driving, sensing and wireless communication vehicle with the remote computer where the control algorithms are processed. We described the main solutions to the problems faced during the development of the platform, especially those of a mechanical and electronics. The problem of navigation and maneuvering back into multi-articulated vehicles is very complex and therefore di cult to solve. A part of this problem is the control setup, which has as objective the achievement and maintenance of certain angles the joints of the vehicle without causing the situation of jackkinife. Thus, as a contribution of control, we propose a controller con guration, named CGPR, which is based on fuzzy theory and uses the original form, the concept of angle of rotation to improve their performance. Were aproach aspects of the dynamics and limitations of movements back as critical angle, and response delays critical con guration. Finally, a version of CGPR with compensating closed loop PID has been implemented and tested in experimental platform developed, which had their results compared to those obtained by other controllers.